Collaborative Problem-Solving Skills of Heterogeneous Groups on Statistics Material Assisted by Microsoft Excel - Wuri Indah Murwaningsih; Tatag Yuli Eko Siswono (Universitas Negeri Surabaya, 2024)
Collaboration is an important skill in the 21st century. This qualitative research is to describe the collaborative problem-solving ability of heterogeneous groups of statistics material assisted by Microsoft Excel. This research is a case study of 2 high and low math ability VIII grade students who were paired into one group in solving statistical problems with Microsoft Excel. The instruments used were math ability tests, problem solving tests, and interviews. Data were analyzed by data reduction, data presentation, and conclusion drawing based on collaborative problem solving ability indicators. The results showed that high mathematics ability students can provide ideas in determining the solution strategy, find Microsoft Excel-assisted solutions, and help low mathematics ability students so that they dominate in the problem solving process. However, low math ability students tend to follow the ideas of high math ability students. There were discussion activities, information sharing, and task sharing in the problem solving process. Therefore, for teachers to improve collaborative solving skills, especially for low math ability students and consider all effective strategies in solving problems.